IMPLEMENTASI PROGRAM BANTUAN PANGAN NON TUNAI TERHADAP KELUARGA PENERIMA MANFAAT DI KELURAHAN BONTODURI KECAMATAN TAMALATE KOTA MAKASSAR - Aspar, Aspar; DN, Syakhruddin (Jurnal Berita Sosial, 2019)
This research was conducted to see how the implementation of the Non-Cash Food Assistance Program (BPNT) for Beneficiary Families (KPM) in Bontoduri Village, Tamalate District. This type of research is qualitative, using the Communication Approach and Social Worker Approach. Data collection methods in this study are observation, interviews and documentation. The instruments used in this study were interview guidelines, documentation tools, and stationery. Data processing techniques and data analysis used in this study include data reduction, data presentation and drawing conclusions.          The results of this study indicate that the Implementation of the Non-Cash Food Assistance Program (BPNT) in the Bontoduri Sub-District of Tamalate has been running quite well and is right on target for the poor who are less able to meet their needs, but to fulfill their monthly needs has not been felt sufficiently. The constraints experienced by beneficiary families include: 1) inaccurate targeting of food aid to beneficiary family accounts, 2) distance between beneficiary families and distant e-warong, 3) inconsistency in the distribution schedule for non-cash food aid, 4) the existence of problems with broken, broken, lost and blocked cards.